Models of industrial symbiosis formation - A. L. Belykh (Управление, 2023)
Industrial symbiosis is actively being developed and implemented in various countries as a tool to reduce the negative impact of business activity on the environment. There are more than 30 implemented examples of industrial symbiosis in the world: Great Britain, Denmark, Norway, Finland, Sweden, Japan, China, USA, Brazil, Russia, etc. Existing studies have determined that the practical implementation of the concept occurs, as a rule, in two ways: chaotically / spontaneously or in a planned mode. The purpose of this study is to identify the main models of the formation and development of industrial symbiosis based on the organizational form of its participants (commercial/non–commercial). The main objectives of the research work are the consolidation and analysis of examples of foreign and Russian practices of forming symbiotic chains, research of organizational forms of participants in existing industrial symbioses, comparative study of identified examples, visualization of chains of potential interactions in various conditions. As a result, five models of industrial symbiosis formation were identified and described. The study may be of interest to industry specialists and experts, facilitators, sustainable development managers and others while planning and forming industrial symbiotic chains in various regions of the Russian Federation.